Reviews and syntheses: On increasing hypoxia in eastern boundary upwelling systems – zooplankton under metabolic stress - L. Frederick; L. Frederick; M. A. Urbina; M. A. Urbina; R. Escribano; R. Escribano (Biogeosciences)
Eastern boundary upwelling systems (EBUSs) are ecologically and economically important marine regions of the world ocean. In these systems, zooplankton play a pivotal role in transferring primary production up through the food web. Recent studies show that global warming is causing a gradual deoxygenation of the world ocean, while in EBUSs, an expansion and intensification of the subsurface oxygen minimum zone (OMZ) is taking place, further exacerbating hypoxic conditions for zooplankton inhabiting the upwelling zone. Hypoxia can affect zooplankton by limiting their aerobic respiration and constraining the migration, energy budget, reproduction, and development. These effects, however, depend on some specific adaptations evolved in habitats, permanently or episodically, subjected to low-oxygen waters. Various metabolic, physiological, behavioural, and morphological adaptations have been described in zooplankton interacting with the OMZ. Adjustment of the aerobic respiration under variable oxygen levels deserves special attention since such adaptive responses to endure mild or severe hypoxia may involve trade-offs in energy usage that impact other metabolic functions or energy-demanding processes. In addition, the oxidative stress resulting from exposure to highly fluctuating oxygen conditions in the upwelling zone can impose further energy expenses. New demands imply a reduction in the energy budget otherwise available for escape, migration, growth, feeding, and reproduction with further ecological consequences for population and community dynamics. This paper reviews and explores the existence or lack of such adaptive metabolic responses along with potential effects of oxidative stress and their role in zooplankton dynamics in EBUSs with major consequences for the pelagic food web and biological productivity.